Notes on australasian orchids 8: Eight new species of Hymenochilus (Cranichideae: Pterostylidinae) and clarification of two previously described species - Jones, David L.; Zimmer, Heidi C.; Clements, Mark A. (Lankesteriana: International Journal on Orchidology, 2024)
Eight new species of Hymenochilus from Australia are described and illustrated. Six of the new species have affinities to (and are here compared with) H. cycnocephalus: H. anemophilus, H. calcicola, H. cymbellus, H. longipes, H. nemoralis and H. pachylus. Hymenochilus anemophilus is shorter (2–8 cm), with dark green strongly veined rosette leaves, crowded dark green flowers, oblong to obovate labellum lamina and, a broader blunter beak on the labellum appendage; H. calcicola is shorter (3–12 cm), crowded green flowers with prominent dark green stripes, ovate petals with a strongly developed basal flange on the anterior side and narrow elliptic labellum lamina with a broad pointed beak on the labellum appendage; H. cymbellus differs by its sparser basal rosette with narrower rosette leaves, thinner scapes, flowers with distinct darker green stripes and shallowly saccate lateral sepals that narrow inwards to a distinctly pointed apex; H. longipes differs by its thin-textured rosette leaves, widely spaced darker green flowers with darker green veins, elliptic-obovate labellum lamina and a longer labellum basal appendage which protrudes prominently from the flower in side view; H. nemoralis has longer rosette leaves, thicker scape and darker green flowers with prominent narrow dark green stripes; H. pachylus has thicker rosette leaves, taller, thicker scape, flowers prominently striped, elliptic-obovate labellum lamina and labellum appendage with a short thick beak. Two of the new species have affinities (and are here compared) with H. muticus: H. pagophilus and H. pisinnus. Hymenochilus pagophilus differs by its moderately crowded to crowded flowers, broader, shinier flowers and rectangular-obovate labellum and H. pisinnus differs by its smaller rosette with smaller, narrower leaves, thinner scape, smaller flowers, that are often on long pedicels, shorter, shallowly saccate lateral sepals, smaller rhomboid petals and, smaller obovate labellum. In addition, Hymenochilus cycnocephalus and H. muticus, are characterised in the strict sense with full descriptions, distribution, and habitat.